Pediatric lupus nephritis - An evil cousin of its adult counterpart: A single-center based experience from a tertiary care hospital of Eastern India - Keya Basu; Subhrajyoti Karmakar; Moumita Sengupta; Arpita Roychowdhury; Alakendu Ghosh; Manimoy Bandopadhyay (Wolters Kluwer Medknow Publications, 2020)
Context: Systemic lupus erythematosus is an autoimmune multisystem disease with a high predilection for renal involvement. Lupus nephritis develops in 20% to 75% within the first two years. Presentation varies from subnephrotic proteinuria to end-stage renal disease. Aims: To study clinical features, biochemical, and serological parameters and correlate with histological activity and chronicity score [modified National Institute of Health (NIH) score]. Settings and Design: Retrospective, cross-sectional, single-center based study in a tertiary care hospital of Eastern India. Subjects and Methods: We incuded 36 children with lupus nephritis diagnosed from February 2018 to March 2019. Laboratory data included were complete blood count (CBC), blood glucose, urine analysis, serum urea, creatinine, blood urea nitrogen (BUN), albumin, cholesterol, HBsAg, antihepatitis C virus (HCV) antibody, antistreptolysin O (ASO) titer, antinuclear antibody (ANA), myeloperoxidase antineutrophil cytoplasmic antibody (MPO ANCA), proteinase 3 antineutrophil cytoplasmic antibody (PR3 ANCA), double-stranded DNA (dsDNA), C3, and C4. Clinical parameters were age, sex, blood pressure (BP), skin lesions, arthralgia, edema, obesity. Renal biopsies examined with light microscopy, hematoxylin and eosin (H and E), periodic acid-Schiff (PAS), silver methanamine, Masson's trichrome (MT) stains. Immunofluorescence microscopy done with IgG, IgM, IgA, C3c, C1q, kappa, lambda antibodies. Statistical Analysis Used: Kruskal-Wallis and χ2 tests. Results: Mean age was 15.12 ± 3.49 and 12.5 ± 1.73 years for lupus nephritis (LN) with activity and LN without activity, respectively. Mean dsDNA was higher and mean C3 was lower (52.35 ± 22.21 mg/dl) in active LN. Mean 24-hour urinary protein was higher in LN without activity. Serum creatinine was raised in active LN. LN class III and IV showed higher activity than chronicity. Conclusions: Pediatric LN is proliferative and more active as compared with adult counterparts. Activity scores are much higher than chronicity scores.